Parâmetros fisiológicos e tricológicos na avaliação do conforto térmico em bovinos de corte - Mastelaro, Ariadne Pegoraro (2016)
This study aimed to evaluate the physiological responses and morphological characteristics of cattle belonging to four different genetic groups with different degrees of heat adaptability, raised in pastures in the Center - West of Brazil. The experiment was conducted in two experimental periods (March and August 2015), at São Carlos Farm, Três Lagoas (MS). 54 calves recently weaned from four genetic groups were used, 14 Nellore, 14 Senepol, 12 ½ Angus x ½ Nelore and 14 ¼ Brahman ¼Nelore x 2/4 Senepol, with age, in the beginning of the experiment, five seven months. The average weight of the animals was 197.0 kg (Nelore), 169 kg (Senepol), 235 kg (½ Angus x ½ Nellore) and 233 kg (¼ Brahman x ¼ Nellore x 2/4 Senepol). The experimental design was completely randomized, with four treatments (breeds), where repetitions are the animals within each genetic group. They measured the temperature (rectal, superficial skin and superficial hair coat), heart rate, respiratory rate and surface skin temperature, surface temperature of fur and sweat rate. Moreover, it was determined some morphologic characteristics of the dorsal region. To characterize the environment, there were collected dry bulb temperature, black globe temperature, dew point temperature, wind speed and relative humidity, the sun and the shade, to determine the following thermal comfort indexes: index temperature and humidity, globe temperature and humidity index, and radiation heat load. Among the adaptive features, only those relating to the present differences between the experimental groups (p <0.05), and the genetic group ½ Angus x ½ Nellore showed the highest values of length, diameter, number of hair, density medium and thickness of the hair coat cover in both evaluation periods (March and August). For physiological variables, there was no statistical difference between the experimental groups (p> 0.05), a fact that was also found in the evaluated periods (p <0.05). It follows, therefore, that the choice of breeds with characteristics consistent with the breeding environment is an important factor in the production system efficiency